Digital game-based learning of domestic safety (esafety) for pre-school - Shuib, Robiah; Azid, Nurulwahida; Yahya, Furiza; Che Man, Suhaini; Yee, Mei Heong; Tee, Tze Kiong; Herawati Herawati, Herawati Herawati (2023)
. Home accidents in children less than 6 years of age mostly occurred due to the negligence of parents or the victims themselves. This study is aimed at educating pre-schoolers on dangerous tools that could be found at home to enable them to identify such items. It is imperative as it could lead to injuries or even worse death if no preventive actions are taken. These interactive learning tools are developed based on constructivism theory, Constructive Alignment Model dan ASSURE Model. Learning Domestic Safety topic in digital Game-Based Learning format for pre-schoolers is constructed using Microsoft PowerPoint Office 2019 software. A combination of Wordwall, quizzes, and digital games are developed and arranged as learning activities. This device emphasizes exciting game-based learning including interactive games such as hidden objects and word wall (maze game and select dangerous items). Such activities could indirectly allow children to learn, identify and avoid dangerous objects which could be found around them in their daily life and at the same time increase their knowledge on domestic safety protection. The children’s cognitive domain and skills are evaluated using word wall (Game Show Quiz and rearrange letters). Mixed-method (combination of qualitative and quantitative) is applied in this study. The study samples comprise 10 academicians who are also expert evaluators from the Institute of Teacher Education Darulaman Campus (IPDA), Sultan Idris Education University, Tanjung Malim, and primary schools in Jitra. Feedbacks from the experts on design and the Digital Game-Based Learning application curriculum are gathered and analyzed to determine the suitability of the developed device. Findings showed that the experts evaluated the application at a moderate range while the reliability score is 0.725